FRI0170 Consensus definitions for mri lesions in the sacroiliac joints of patients with axial spondyloarthritis: first analysis from the assessments in spondyloarthritis international society (ASAS) classification cohort. (12th June 2018) - Maksymowych, W.P.; Pedersen, S.J.; Baraliakos, X.; Machado, P.; Weber, U.; Sieper, J.; Wichuk, S.; Poddubnyy, D.; Østergaard, M.; Lambert, R.G.
Abstract : Background: A broad spectrum of MRI lesions has been described in the sacroiliac joint (SIJ) of patients with axial spondyloarthritis and a recent consensus from the ASAS MRI group has culminated in updated lesion definitions (ASAS_MRI_def n ). There has been no central reader evaluation of MRI scans from the ASAS Classification Cohort (ASAS-CC) 1 to determine the spectrum of MRI lesions in the SIJ in this cohort, to compare the frequencies of different lesion types, and to compare detection of lesions between central and ASAS-CC local site readers Objectives: To determine the spectrum and compare the frequencies of active and structural lesions on MRI images from the ASAS-CC according to the consensus ASAS_MRI_def n update. Methods: ASAS_MRI_def n were recorded in an eCRF that comprises global assessment (lesion present/absent) and detailed scoring (SPARCC SIJ inflammation, SPARCC SIJ structural). For global assessment, wording of lesions defining active and structural lesions typical of axSpA was the same as in the original ASAS-CC eCRF permitting comparisons between central and local site readers. MRI images were available in a variety of formats (DICOM (n=175), JPEG(n=71), DICOM film(n=32)) and sequences, axial and semicoronal orientations, from 278 of the 495 cases who had MRI performed in the ASAS-CC. Image quality was considered sufficient to record global data by 6 central readers in all cases. An additional reader assessed only images in DICOM format (n=175). Detailed SPARCC scoring data was based only on assessment of images in DICOM format. Comparison of active and structural lesion frequencies was assessed descriptively according to individual and majority of central readers data. Detection of active lesions typical of axSpA in all available images from the ASAS-CC was compared between central and local readers. Results: The percentage of cases with active lesions typical of axSpA recorded by central readers (28.4% by majority read) was lower than the 40% reported by local site readers in the ASAS-CC (table 1). This was similar to the frequency of structural lesions typical of axSpA (28.6% by majority read) (table 2). 11.2% had subchondral inflammation but not active lesions typical of axSpA but only 0.3% had active lesions typical of axSpA without subchondral inflammation. Erosion was the most frequently observed structural lesion (25.2%) followed by fatty lesion (19.8%). Results were very similar when only data from the 175 DICOM cases was analysed. Conclusions: In this first central reader analysis of MRI images from the ASAS-CC we demonstrate similar frequencies of active and structural lesions typical of axSpA, erosion as a common lesion, some degree of false positive subchondral inflammation, and a lower frequency of active lesions typical of axSpA than noted by local site readers. Reference: [1] Rudwaleit, et al. Ann Rheum Dis2009;68:777–831. Disclosure of Interest: None declared